Using Vocabulary Journals to Improve Vocabulary Learning among Primary School Pupils in Malaysia - Li Li Kee; Joanna Chong Wan Ting (Journal of English Education, 2019)
This action research was to investigate the effects of vocabulary journals on Malaysian primary school pupils’vocabulary learning. English language learners (ELLs) are often unable to retain new vocabulary learning. This could be attributed to the fact that the traditional method of vocabulary learning does not appeal to them in terms of engagement and interest. Therefore vocabulary journals were conceived as an interesting and engaging method to improve pupils’ vocabulary learning. The action research design was used which integrated both qualitative and quantitative data (i.e., pupils’ work, semi-structured interview, pre-vocabulary test, and post-vocabulary test). The results show that vocabulary journals helped the participants to learn vocabulary more effectively. It is an effective scaffolding tool for vocabulary learning among the primary school pupils, though the journals could be further improved. Further suggestions were to improve on the questions in interviewing and to use reflective journals to increase the validity of the research.